2003
DOI: 10.1029/2002pa000803
|View full text |Cite
|
Sign up to set email alerts
|

Physiological impacts on alkenone paleothermometry

Abstract: [1] We conducted isothermal (15°C) batch culture experiments with the coccolithophorid Emiliania huxleyi (strain NEPCC 55a) to evaluate the extent to which nutrient and light stress contribute to variability in the alkenone unsaturation index U 37 K 0. Alkenone content and composition were constant throughout exponential growth in both experiments when nutrients (nitrate and orthophosphate) were replete. Stationary phase (nutrientstarved) cells continued to produce alkenones, amassing concentrations (AEAlk) ! … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 32 publications
14
129
1
1
Order By: Relevance
“…In exponentially growing cells alkenones comprise between 2% and 20% of total cellular carbon (Prahl et al, 1988;Pond and Harris, 1996;Conte et al, 1998). Under nutrient stress, values up to 39% have been reported (Prahl et al, 2003). This is in very good agreement with the results of our experiment, assuming that cellular concentrations of total organic carbon in E. huxleyi range from 6 to 15 pg cell À1 in exponentially growing cells (Riebesell et al, 2000;Zondervan et al, 2002;Prahl et al, 2003) and up to 22 pg cell À1 under stationary phase conditions Van Bleijswijk et al, 1994;Riegman et al, 2000).…”
Section: Isotopic Fractionation In E Huxleyi and Pocsupporting
confidence: 82%
See 1 more Smart Citation
“…In exponentially growing cells alkenones comprise between 2% and 20% of total cellular carbon (Prahl et al, 1988;Pond and Harris, 1996;Conte et al, 1998). Under nutrient stress, values up to 39% have been reported (Prahl et al, 2003). This is in very good agreement with the results of our experiment, assuming that cellular concentrations of total organic carbon in E. huxleyi range from 6 to 15 pg cell À1 in exponentially growing cells (Riebesell et al, 2000;Zondervan et al, 2002;Prahl et al, 2003) and up to 22 pg cell À1 under stationary phase conditions Van Bleijswijk et al, 1994;Riegman et al, 2000).…”
Section: Isotopic Fractionation In E Huxleyi and Pocsupporting
confidence: 82%
“…Physiological factors such as nutrient availability (e.g., Epstein et al, 1998;Prahl et al, 2005) as well as genetic differences (e.g., Conte et al, 1998;Popp et al, 2006) have been suggested in order to explain this phenomenon. In a recent culture experiment at constant temperature (15°C), Prahl et al (2003) found a decline of U K 0 37 values by 0.11 units following growth limitation by nutrient depletion. This decrease in U K 0 37 was accompanied by an increase in cellular alkenone concentration from 1.5-2 to 6 pg cell À1 which is nearly identical to the values observed in the present study (Fig.…”
Section: Alkenonesmentioning
confidence: 99%
“…Loebl et al, 2010), and might result in an increase in the production and storage of alkenones (e.g. Eltgroth et al, 2005;Prahl et al, 2003). Alkenone temperature records from the Subtropical Front at the Chatham Rise, south-western Pacific Ocean (Sikes et al, 2005), showed that biases occurred during times of highest lipid fluxes and low nutrient conditions in the surface mixed layer.…”
Section: Production and Export Within The Surface Layer Of The Eddymentioning
confidence: 99%
“…Batch culture experiment have demonstrated that the cell alkenone content, as well as the U K 37 , may be significantly affected by environmental conditions like nutrient or light stress, as well as stationary or exponential growth phases (e.g. Epstein et al, 1998;Prahl et al, 2003). The quantity of alkenone per cell may vary as a function of growth conditions and therefore be unequal from one habitation depth to another.…”
Section: Production Depthmentioning
confidence: 99%